Self-Reported Lifetime Violence Exposure and Self-Compassion Associated With Satisfaction of Life in Historically Black College and University Students - Blanden, Gwenna (Journal of interpersonal violence, 2021)
In the United States, approximately 25% of minors have witnessed a violent act, specifically physical assault. African Americans from under-served backgrounds are more likely than other racial and ethnic groups to be exposed to traumatic events. However, there is scant literature examining violence exposure, SC, and life satisfaction collectively, specifically in an African American college sample. The current study sought to determine the associations among violence exposure, SC components, and life satisfaction in an African American college sample. The current sample was comprised of 356 participants (80% female) with a mean age of 20.23 (SD = 1.70). Eighty-eight participants (25%) reported being exposed to violence in their lifetime. Employing logistic regression, we determined violence exposed individuals were less likely to report high satisfaction of life than their non-exposed counterparts (OR = 0.58, 95% CIs = 0.33, 1.00). Individuals with high level of self-kindness were approximately two times more likely to have higher satisfaction of life (OR = 2.48; CI = 1.52, 4.05) compared to their low level self-kindness counterparts and in the presence of demographic covariates. These findings may educate and increase awareness of the impacts of traumatic events. This education could lead to the implementation of interventions to build upon overall well-being in order increase life satisfaction in college students.